Beberapa Faktor yang Berisiko Terhadap Hipertensi pada Pegawai di Wilayah Perimeter Pelabuhan (Studi Kasus Kontrol di Kantor Kesehatan Pelabuhan Kelas II Semarang) - Eka Oktaviarini; Suharyo Hadisaputro; Ari Suwondo; Henry Setyawan (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2019)
Background: Hypertension is an increase in arterial blood pressure where systolic blood pressure is ≥140 mmHg or diastolic blood pressure ≥90 mmHg. Hypertension is often called the silent killer because it does not cause symptoms so the treatment is often late. Occupational-related diseases one of which is hypertension. The type of work, work environment, lifestyle and individual characteristics can be a factor of hypertension.Methods: An analytical observational study using a case-control design with 76 samples consisting of 38 cases and 38 controls taken by consecutive sampling. The variables studied were age, gender, family history, type of work, years of work, workload, work schedule, sedentary behavior, coffee drinking habits, and smoking habits. Data were analyzed by bivariate and multivariate with logistic regression method.Results: Significant factors for hypertension were sex (p=0,012; OR adjusted 6,582; 95% CI 1,522-28,456) and the work type (p=0,020; OR adjusted 5,248; 95%CI 1,292-21,316) as risk factors, while sedentary behavior (p=0,030; OR adjusted 0,311; 95% CI 0,108-0,895) as a protective factor. The factors that are not significant at risk are age, family history, years of work, workload, work schedule, coffee drinking habits and smoking habits.Conclusion: Male and structural work type are risk factors, while sedentary behavior ≥ 6 hours/day is a protective factor. Probability at risk of hypertension is 75%.